Maize yields in reliance on fertilizers and hybrids on dark gray ashed soils - Єрмакова, Л. М.; Крестьянінов, Є. В. (Scientific Progress & Innovations, 2016)
The results of studies of the influence of foliar feeding crops of corn water-soluble fertilizer «Nutrimiks», «Nutribor» and «Micro-Mineralis» on background calculation rules N158P52K52 complete mineral fertilizer (background) on the yield and quality of corn grain are presented. It was found that the use of foliar feeding on the background of the main fertilizer has a positive effect on the performance of the studied maize hybrids. Based on the analysis of the research results revealed that optimizing nutrition contributes to more complete disclosure of the resource potential of plants and higher yields.